THE SELECTION OF ZAKAT FUNDRAISING ACTIVITIES OF ZAKAT MANAGEMENT ORGANIZATIONS IN EAST JAVA USING ANALYTIC NETWORK PROCESS - Noven Lukito Hadi Saputro; Raditya Sukmana (Universitas Airlangga, 2020)
There are various methods in which zakat management organizations carry out fundraising activities. The most common methods are direct and indirect fundraising. This study aims to select the most dominant fundraising activities for zakat management organizations in East Java. This study uses a qualitative approach with the Analytic Network Process method. This study uses the BOCR model (Benefit, Opportunity, Cost, Risk). The results of this study found that the most dominant alternative in East Java is Direct Fundraising, with a priority value of 37.90% (W = significant). Then, the second alternative is digital fundraising (25.11%, W = significant) and the third alternative is indirect fundraising (17.12%, W = significant).Keywords: Fundraising Activities, Zakat Management Organizations, Analytic Network ProcessREFFERENCE Amanda, G. (2018). Penghimpunan zakat Baznas 2018 naik 31,8 persen. Retrieved March 19, 2019, from https://www.republika.co.id/berita/dunia-islam/wakaf/18/12/28/pkfx0i423-penghimpunan-zakat-baznas-2018-naik-318-persenAscarya. (2005). Analytic Network Process (ANP): Pendekatan baru studi kualitatif. Jakarta: Center for Central Banking Education and Studies, Bank Indonesia.Ascarya. (2013). Determining the real causes of financial crisis in Islamic economic perspective: Analytic Network Process (ANP) Approach. Tazkia Islamic Finance and Business Review, 9(2), 109-127BAZNAS. (2017). Statistik zakat nasional (2nd ed). Jakarta: BAZNAS.Firdaus, M. dkk. (2012). Economic estimation and determinations of zakat potential in Indonesia. Islamic Research and Training Institute. https://doi.org/10.1002/mop.23534Hasanah, U. (2015). Sistem fundraising zakat lembaga pemerintah dan swasta (studi komparatif pada badan amil zakat nasional (BAZNAS) kota Palu dan pos keadilan peduli umat (PKPU) Palu periode 2010-2014). ISTIQRA, 3(2), 226–249.Heyman, D. R., & Brenner, L. (2016). Non profit fundraising 101. New Jersey: John Wiley & Sons, Inc.Marwing, A. (2015). Pendekatan psikologi dalam peningkatan fundraising zakat. AN-NISBAH, 2(1), 199-226.Purwakananta, M. A. (2008). Strategi fundraising. Materi Presentasi Dompet Dhuafa.Safitri, K. (2018). BAZNAS targetkan perolehan zakat tahun ini tembus Rp 8 triliun. Retrieved March 19, 2019, from https://nasional.kontan.co.id/news/baznas-targetkan-perolehan-zakat-tahun-ini-tembus-rp-8-triliunTempel, E. R., Seiler, T. L. ., & Aldrich, E. E. (2011). Achieving excelence in fundraising. San Francisco: Jossey-Bass.